Computational investigation on turbulent heat transfer of supercritical CO2 in the half-roughen horizontal pipe - Yang, Jun; Xie, Xiongzhou; Tang, Guowei; Wang, Jianyong (Frontiers in Energy Research, 2023)
To address the degraded heat transfer that occurs in the top section of horizontal pipes when sCO2 fluid flows are heated, the upper half wall with higher temperatures is particularly roughened using uniform sand-grain roughness. The SST k-ω model is validated then used to simulate the horizontal sCO2 heat transfer involving a variety of operating parameters and roughness heights. Results indicate that the half-roughen scheme is effective in significantly reducing higher temperatures of the entire upper wall and improving heat transfer homogeneity. The roughness height plays a crucial role and an optimal value exists, which is largely influenced by the buoyancy strength and its local variations of horizontal sCO2 flows under different conditions.